Penerapan Metode Speed Reading untuk Meningkatkan Hasil Belajar Siswa Kelas V pada Mata Pelajaran Bahasa Indonesia (Universitas Negeri Makassar, 2023)
The problem of this research is the low student learning outcomes in Indonesian language subjects. The aim of this research is to describe the application of the Speed Reading method to improve the learning outcomes of class V students in the Indonesian language subject at SDN 17 Bajoe, East Tanete Riattang District, Bone Regency. The approach in this research is a descriptive qualitative approach. This type of research is recycling PTK. The focus of this research is 1) Application of the Fast Reading method, 2) Student learning outcomes. The subjects in the research were class V students at UPT SD Negeri 17 Bajoe, East Tanete Riattang District, Bone Regency. The subjects in this research were 25 students consisting of 12 men and 13 women. The data collection techniques used are observation, tests and documentation. The data analysis techniques in this research are data reduction, data presentation and drawing conclusions. The research results show an increase. Cycle I achieved Good qualifications (B) and in cycle II achieved Very Good qualifications (A). The conclusion of this research is that applying the Speed Reading method can improve student learning outcomes in Indonesian language subjects in Class V of SD Negeri 17 Bajoe, East Tanete Riattang District, Bone Regency.